2015
DOI: 10.1097/inf.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary and Systemic Pharmacokinetics of Colistin Following a Single Dose of Nebulized Colistimethate in Mechanically Ventilated Neonates

Abstract: The purpose of this study was to evaluate the pulmonary and systemic pharmacokinetics of colistin following a single dose of nebulized colistimethate sodium (CMS) in mechanically ventilated neonates. We administered a single dose of nebulized CMS (approximately 120,000 IU/kg of CMS, equivalent to 4 mg/kg colistin base activity) to 6 ventilated neonates with ventilator-associated pneumonia. The median gestational age was 39 weeks (range, 32-39 weeks). Mean (± SD) tracheal aspirate colistin maximum concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Serum biochemical parameters of samples were evaluated for alkaline phosphatase (ALP), aspartate transaminase (AST), urea nitrogen (UN), glucose (GLU), total protein [ 30 ], albumin (ALB), globulin (GLO), calcium (Ca), phosphate (P), using an automatic biochemical analyzer (7180ISE, Japan Hitachi High-Tech, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Serum biochemical parameters of samples were evaluated for alkaline phosphatase (ALP), aspartate transaminase (AST), urea nitrogen (UN), glucose (GLU), total protein [ 30 ], albumin (ALB), globulin (GLO), calcium (Ca), phosphate (P), using an automatic biochemical analyzer (7180ISE, Japan Hitachi High-Tech, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Over the last decade, nebulization of colistin has become an alternative in treating MDR Gram-negative respiratory tract infections (10,11). Inhalation therapy of colistin reduces systemic exposure and thus minimizes potential systemic side effects such as nephrotoxicity (1,12). PK studies in rats (6)(7)(8) and cystic fibrosis patients (9) have clearly demonstrated that nebulization of CMS/colistin resulted in much higher drug exposure in the epithelial lining fluid (ELF) or sputum than by systemic administration.…”
mentioning
confidence: 99%
“…Only recently has the importance of aerosolized polymyxins for the treatment of respiratory tract infections started attracting significant interest (17)(18)(19)(20)(21)(22)(23)(24). The majority of current preclinical and clinical PK/PD data for aerosolized polymyxins focus on CMS/colistin (12,19,21,22,(25)(26)(27), although aerosolized polymyxin B has also been used in the clinic (28).…”
mentioning
confidence: 99%